2011
DOI: 10.1016/j.yjmcc.2010.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin normalises peripheral cardiac sympathetic hyperactivity in the spontaneously hypertensive rat

Abstract: Hypertension is associated with heightened cardiac sympathetic drive whilst statins reduce angiotensin II (ATII) signalling, superoxide anion production and increase nitric oxide bioavailability, events that can potentially reduce peripheral cardiac sympathetic neurotransmission. We therefore investigated whether pravastatin alters peripheral cardiac sympathetic control in the spontaneously hypertensive rat (SHR). SHRs (16–18 weeks) had significantly (p < 0.05) enhanced atrial 3H-norepinephrine (3H-NE) release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 36 publications
4
36
1
Order By: Relevance
“…This possibility was supported by our and other's studies, which indicated that the AT1 blocker, losartan, can inhibit prostate hyperplasia in SHRs [21,23]. A previous study has shown that statin can normalize sympathetic hyperactivity in SHR [24]. However, simvastatin failed to influence the Ang-II serum levels in the present experiment.…”
Section: Discussionsupporting
confidence: 81%
“…This possibility was supported by our and other's studies, which indicated that the AT1 blocker, losartan, can inhibit prostate hyperplasia in SHRs [21,23]. A previous study has shown that statin can normalize sympathetic hyperactivity in SHR [24]. However, simvastatin failed to influence the Ang-II serum levels in the present experiment.…”
Section: Discussionsupporting
confidence: 81%
“…Experimental studies have shown that statins can influence sympathetic activity. 27 However, since statins had no effect on the risk of heart failure in the PROSPER trial during the study period, it seems unlikely that the association between heart rate and heart failure is influenced by statins. 14 Our study also has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, in SHRs (spontaneously hypertensive rats), 2 weeks of pravastatin [100 mg/l (in drinking water)], a hydrophilic statin, did not alter plasma cholesterol or BP, but reduced HR [74]. An accompanying in vitro study of the right atrium found that pravastatin diminished the release of pre-loaded tracerlabelled [ 3 H]-NE to that of the WKY control rats.…”
Section: Hypertensionmentioning
confidence: 98%